2022
DOI: 10.12740/pp/onlinefirst/127217
|View full text |Cite
|
Sign up to set email alerts
|

Mental health of medical workers during COVID-19 pandemic - literature review.

Abstract: Niedawno odkryta choroba COVID-19 jest spowodowana przez koronawirusa ostrej niewydolności oddechowej 2 (SARS-CoV-2). Światowa Organizacja Zdrowia ogłosiła globalną pandemię 11 marca 2020 r., a sam COVID-19 stał się klinicznym zagrożeniem dla populacji ogólnej i pracowników służby zdrowia na całym świecie. Niniejszy przegląd literatury opisuje wpływ COVID-19 na zdrowie psychiczne personelu medycznego. Dotychczasowe badania są nieliczne, w większości koncentrują się na depresji, lęku i bezsenności. Według doni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
1
10
1
Order By: Relevance
“…During the COVID-19 epidemic, health professionals, directly engaged in fight against COVID-19, experience chronic fatigue and stress ( Hammami et al, 2021 ). Medical workers also display compassion fatigue, burnout ( Gawrych, 2021 ; Neto et al, 2020 ), and mental exhaustion ( Alharbi, Jackson & Usker, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 epidemic, health professionals, directly engaged in fight against COVID-19, experience chronic fatigue and stress ( Hammami et al, 2021 ). Medical workers also display compassion fatigue, burnout ( Gawrych, 2021 ; Neto et al, 2020 ), and mental exhaustion ( Alharbi, Jackson & Usker, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of our study, more than half of the respondents indicated a lack of psychological support in the workplace. According to the study of Kang et al [1], in terms of psychological support, 36.3% of the respondents received written psychoeducational materials (i.e., pamphlets, brochures and books), half of the respondents received psychological support through the media (which included online psychological support, as well as information obtained through television and online platforms) and 17.5% participated in group psychological counseling. It was noted that the higher the level of exposure to COVID-19 patients, the more severe the mental health disorders [23].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of reliable information and detailed procedures, limitations related to the scarcity of protective measures and, perhaps most importantly, initial diagnostic difficulties resulting from the lack of access to virus-confirming tests and long waiting periods for their results caused tension, fatigue and a sense of overload. These elements may have resulted in symptoms of anxiety, depression, sadness and insomnia [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…As far as protecting the mental health of medical professionals is concerned, the significant problem lies in lack of public support, which has been pointed out by 9,5% of respondents. This is a crucial element, which stands unnoticed during the current pandemic situation, and even underestimated by employers [19,20]. There is an extensive discussion focusing on the issue of abandoned hospitalized patients, dying alone, isolation of patients, at the same time disregarding the personnel and their real, existing mental health issues that they are experiencing.…”
Section: Discussionmentioning
confidence: 99%